Intelektualizm w etyce Tadeusza Stycznia - FRYDRYCH, Jacek (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
The ethics developed by Tadeusz Styczeń is a variant of ethical personalism. He holds that the source of moral duty is truth and the dignity of the human person. In the current article, I present Styczeń’s fundamental theses which point to his ethical intellectualism. I also present an analysis of ethical intellectualism and demonstrate that Styczeń’s ethics can be perceived as its moderate version, while it is not intellectualist in the extreme sense of the term. To conclude, I demonstrate that the presented understanding of ethics is essentially internalist. Translated by Dorota Chabrajska